Komunikasi Parasosial Dai Milenial: Strategi Intimasi di Instagram dan Tiktok - Famuji, Untung; Nurhaidah, Siti Nuri; Pramula, Beni; Yasin, Fikri (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2025)
This study examines parasocial communication between millennial dai and their audiences on Instagram and TikTok within the context of digital Islamic preaching. The shift of da‘wah from conventional spaces to social media not only transforms the medium of religious communication but also reshapes communicative relations, intimacy construction, and the legitimation of religious authority. This study aims to analyze the strategies of parasocial intimacy construction employed by millennial dai and to compare how these strategies differ across Instagram and TikTok. Adopting a qualitative approach, this research employs digital netnography, multimodal content analysis, and audience reception interviews. Data were collected through sustained observation of five popular millennial dai, analysis of high-engagement Instagram posts and TikTok videos, and semi-structured interviews with active followers. The findings reveal that millennial dai employ six primary intimacy construction strategies: personal self-disclosure, interactive responsiveness, relatable informal language, emotional storytelling, behind-the-scenes content, and participation in digital trends. Cross-platform analysis shows that Instagram tends to foster curated and aspirational intimacy, whereas TikTok produces intimacy that appears spontaneous through casual expression and viral culture. However, the study demonstrates that such authenticity is performative and strategically adapted to platform-specific affordances. The findings further indicate that digital intimacy does not necessarily dilute religious messages, but rather transforms hierarchical preacher–audience relations into more fluid and communicative forms. At the same time, millennial dai operate within the logic of the attention economy and micro-celebrity culture, which may strengthen audience attachment while also posing risks of religious commodification and persona-centered devotion. Theoretically, this study contributes to parasocial communication scholarship within digital religion studies; practically, it offers a critical understanding of contemporary Islamic preaching in social media environments.